2010
DOI: 10.1103/physrevb.81.115402
|View full text |Cite
|
Sign up to set email alerts
|

Metastable surface oxide on CoGa(100): Structure and stability

Abstract: We investigated the structure and formation of a surface oxide and bulk ␤-Ga 2 O 3 on CoGa͑100͒ from ultrahigh vacuum to 1 bar oxygen pressure in a temperature range from 300 to 1040 K. We combined in situ surface x-ray diffraction with scanning tunneling microscopy, atomic force microscopy, and density-functional theory calculations. We find that the two-dimensional epitaxial surface oxide layer exhibits a p2mm symmetry with an additional mirror plane as compared to the bulk oxide. The surface oxide layer is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2012
2012
2014
2014

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 43 publications
(37 reference statements)
0
2
0
Order By: Relevance
“…Such a significant difference is attributed to the effect of kinetic hindrance that prevents the surface from establishing equilibrium with the imposed oxygen chemical potential. In fact, the significant discrepancy between equilibrium phase diagram predictions and experimental realities was also observed on Cu (100), and also similar kinetic hindrance effects were observed for other metallic systems. For instance, Lundgren et al performed an in situ study on the oxidation of Pd(100) surface at oxygen pressures in the range of 10 –6 –10 3 mbar using surface X-ray diffraction and noted the strong kinetic hindrance to bulk oxide formation from an oxygen chemisorbed phase even at a temperature as high as 675 K …”
Section: Introductionmentioning
confidence: 73%
“…Such a significant difference is attributed to the effect of kinetic hindrance that prevents the surface from establishing equilibrium with the imposed oxygen chemical potential. In fact, the significant discrepancy between equilibrium phase diagram predictions and experimental realities was also observed on Cu (100), and also similar kinetic hindrance effects were observed for other metallic systems. For instance, Lundgren et al performed an in situ study on the oxidation of Pd(100) surface at oxygen pressures in the range of 10 –6 –10 3 mbar using surface X-ray diffraction and noted the strong kinetic hindrance to bulk oxide formation from an oxygen chemisorbed phase even at a temperature as high as 675 K …”
Section: Introductionmentioning
confidence: 73%
“…Therefore, detailed study of the oxidation behavior under practical gas conditions is highly desired, and some recent studies revealed the reaction mechanisms can be indeed significantly different between UHV conditions and ambient gas pressures. 5,[18][19][20][21][22][23][24][25][26][27][28] In this work, we study the oxidation of Cu-Au(100) alloys under the realistic conditions of the oxygen gas pressure varying from 5 Â 10 -5 to 760 Torr by investigating the effect of alloying Cu with Au on the nucleation orientations of oxide islands. Our study reveals a transition from nucleating epitaxial Cu 2 O nanoislands to non-epitaxial oxide islands upon increasing the oxygen gas pressure, and this pressure depends sensitively on the Au mole fraction in the Cu-Au alloys.…”
Section: Introductionmentioning
confidence: 99%